CORRELATION BETWEEN PERIODONTAL AND MICROBIOLOGICAL STATUS AT PATIENTS WITH FIXED PROSTHETIC THERAPY - Marius Andrei Dinu; Adriana Preda; Anca Dumitriu; Horia Traian Dumitriu; Imelda Ramona Dinu (Romanian Society of Oral Rehabilitation, 2014)
Aim of the study Benzoyl-DL-arginine-naphthylamide test (BANA) has been used by many researchers to quickly screen the contribution of red complex periodontal pathogens in patients with fixed prosthetics dentures. The purpose of this study was to determine periodontal pathogens BANA-positive to patients with fixed prosthesis made by cobalt-chromium alloys and nickel-chromium. Material and methods Before applying the prosthetic treatment, the score sheet was recorded, probing depths were measured and plaque samples were taken for laboratory analysis. Plaque samples were collected from each quadrant from the interproximal area between the primary molars and secondary premolars. After were taken the plaque samples for BANA test, were measured the depth of periodontal pockets of the selected teeth and plaque scores. The score board was then assessed using the index plaque O'Leary. Results and discussions This study found an increase in average of pocket depth during prosthetic treatment.The differences were generally small, but significant between visits 3, 4, and 5 versus baseline.Probing depths and scores plaque were more uniform growth after placing prosthetic devices. Also our study showed an increase in scores BANA prosthetic treatment.The scores at visits 2-5 were significantly higher than baseline, showing the largest increase in four months from applying of prosthetic treatment. BANA test was shown to be an reliable indicator for the presence of three suspected periodontal pathogens (red complex): P gingivalis, T denticola, and T forsythia. These bacteria have been linked to common forms of periodontal disease in adults. BANA test showed the presence of periodontal pathogens from all patients, with variations in the detected levels. Results showed over time statistically significant differences in BANA scores to adult patients undergoing prosthetic therapy. Conclusions In this study was detected a simultaneous increase of BANA - positive periodontal pathogens - P gingivalis, T denticola, and T forsythia during prosthetic treatment especially with Cr-Co alloys.